Building e-Agriculture framework in Kenya - Awuor, Fredrick; Raburu, George; Onditi, ArvinLucy A.; Rambim, Dorothy (HAAI, 2016)
Arguably, poverty is concentrated in developing countries due to poor capacity to develop, to access and to manage agricultural information and knowledge. This is owed to disconnect that exist between the e-Agricultural products available in the market and the information needs of the farmers. To address this challenge, there is need to integrate information required by the farmers from the diverse to a single information access point. Such an access point need to be pervasive enough to provide anywhere, anytime and any device information access while meeting the need to avail timely, relevant, accurate and consumable information to farmers. In this paper we attempt to build such an information access point. Specifically, we establish information needs of farmers in Kenya and strategies to bridge these needs in attempt to improve agricultural productivity. We then illustrate that addressing these needs require strict considerations to interests of stakeholders in agriculture as we show that it is critical that the agricultural stakeholders cooperate and collaborate, that is working jointly toward maximizing whole-some agricultural output and individual benefits. And consequently we develop an integrated framework for e-Agriculture adoption based on the agriculture-stakeholder consortium that models stakeholders’ interests.
Keywords: E-Agriculture; ICT-in Agriculture; Stakeholders; Framework; Model